Extent of ESG disclosure for energy sector companies: ESG reporting guide 2.0 Nasdaq - Juli Riyanto Tri Wijaya; Eliada Herwiyanti (Universitas Muhammadiyah Malang, 2024)
Purpose: The aim of this research is to assess the extent to which energy sector companies have disclosed ESG-related information in their annual reports in 2021 and 2022. Methodology/approach: This research uses secondary data obtained from company annual reports accessed via the Indonesia Stock Exchange website and the official websites of related companies. ESG is measured using indicators from Nasdaq's ESG Reporting Guide 2.0, which consists of a total of 30 measurement indicators. Findings: The research results show that energy sector companies listed on the IDX in 2021 and 2022 have implemented extensive ESG disclosures to the public. Practical and Theoretical contribution/Originality: ESG-related information can be used as additional analysis material for investors before deciding to invest in the company. In this way, investors can understand the impacts and efforts made by the company as a result of operational activities that can have an impact on the environment. The findings of this research can also provide a reference for the government in formulating policies regarding the impact of energy sector company activities on environmental sustainability. Meanwhile, for academics, this research can be used as a reference and reference for similar research in the future. Research Limitation: This research has limitations in the level of subjectivity when searching for information in annual reports. This subjectivity is caused by the use of keywords used by each researcher which can be different. Future research could use other sector areas to assess the extent of ESG disclosure in company annual reports.